Range livestock production systems: Development, monitoring, research. A briefing note with special reference to Botswana and communal areas research - International Livestock Centre for Africa (International Livestock Centre for Africa, 1982)
Presents papers on the development of range livestock production systems, dealing with aspects such as monitoring & the systems approach. Describes traditional livestock production systems in inter-tropical Africa & esp. in Botswana, showing their experience in livestock development projects. Examines the social & environmental impact of Botswana's national Tribal Grazing Land Policy (TGLP), & discusses the importance of carrying out research on TGLP issues & on animal production in order to improve existing production systems. Considers ILCA's mandate, its involvment & role in the development of an East African Range Livestock systems studies' network, taking into account experiences in Kenya & Botswana.